# |
ODE |
Mathematica |
Maple |
\[
{}\left (a^{2}-x^{2}\right ) {y^{\prime }}^{2}-2 x y y^{\prime }-y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (a^{2}+x^{2}\right ) {y^{\prime }}^{2}-2 x y y^{\prime }+b +y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} {y^{\prime }}^{2}-4 x y y^{\prime } = 8 x^{3}-y^{2}
\] |
✓ |
✓ |
|
\[
{}a \,x^{2} {y^{\prime }}^{2}-2 a x y y^{\prime }+a \left (1-a \right ) x^{2}+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (-a^{2}+1\right ) x^{2} {y^{\prime }}^{2}-2 x y y^{\prime }-a^{2} x^{2}+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} {y^{\prime }}^{2} = a
\] |
✓ |
✓ |
|
\[
{}x^{3} {y^{\prime }}^{2}+x y^{\prime }-y = 0
\] |
✓ |
✗ |
|
\[
{}x^{3} {y^{\prime }}^{2}+x^{2} y y^{\prime }+a = 0
\] |
✓ |
✓ |
|
\[
{}x \left (-x^{2}+1\right ) {y^{\prime }}^{2}-2 \left (-x^{2}+1\right ) y y^{\prime }+x \left (1-y^{2}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}4 x \left (a -x \right ) \left (-x +b \right ) {y^{\prime }}^{2} = \left (a b -2 x \left (a +b \right )+2 x^{2}\right )^{2}
\] |
✓ |
✓ |
|
\[
{}x^{4} {y^{\prime }}^{2}-x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x^{4} {y^{\prime }}^{2}+2 x^{3} y y^{\prime }-4 = 0
\] |
✓ |
✓ |
|
\[
{}x^{4} {y^{\prime }}^{2}+y^{2} y^{\prime } x -y^{3} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} \left (a^{2}-x^{2}\right ) {y^{\prime }}^{2}+1 = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{4} {y^{\prime }}^{2}-x y-y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{5} {y^{\prime }}^{2}+12 x^{4} y y^{\prime }+9 = 0
\] |
✓ |
✓ |
|
\[
{}x^{6} {y^{\prime }}^{2}-2 x y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{8} {y^{\prime }}^{2}+3 x y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2} = a
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2} = x \,a^{2}
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2} = {\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}+2 a x y^{\prime }-a y = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}-4 a^{2} x y^{\prime }+a^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}+a x y^{\prime }+b y = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}-\left (-2 b x +a \right ) y^{\prime }-b y = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}+x^{3} y^{\prime }-x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}+\left (x -y\right ) y^{\prime }-x = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}-\left (x +y\right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}-\left (x y+1\right ) y^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}+\left (x -y^{2}\right ) y^{\prime }-x y = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}+y = a
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right ) {y^{\prime }}^{2}+2 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 x -y\right ) {y^{\prime }}^{2}-2 \left (1-x \right ) y^{\prime }+2-y = 0
\] |
✓ |
✓ |
|
\[
{}2 y {y^{\prime }}^{2}+\left (5-4 x \right ) y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}9 y {y^{\prime }}^{2}+4 x^{3} y^{\prime }-4 x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}\left (1-a y\right ) {y^{\prime }}^{2} = a y
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-a y\right ) {y^{\prime }}^{2}-2 x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y {y^{\prime }}^{2}+\left (x +y\right ) y^{\prime }+1 = 0
\] |
✓ |
✓ |
|
\[
{}x y {y^{\prime }}^{2}+\left (x^{2}+y^{2}\right ) y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}x y {y^{\prime }}^{2}+\left (x^{2}-y^{2}\right ) y^{\prime }-x y = 0
\] |
✓ |
✓ |
|
\[
{}x y {y^{\prime }}^{2}-\left (x^{2}-y^{2}\right ) y^{\prime }-x y = 0
\] |
✓ |
✓ |
|
\[
{}x y {y^{\prime }}^{2}+\left (a +x^{2}-y^{2}\right ) y^{\prime }-x y = 0
\] |
✓ |
✗ |
|
\[
{}x y {y^{\prime }}^{2}-\left (a -b \,x^{2}+y^{2}\right ) y^{\prime }-b x y = 0
\] |
✓ |
✗ |
|
\[
{}x y {y^{\prime }}^{2}+\left (3 x^{2}-2 y^{2}\right ) y^{\prime }-6 x y = 0
\] |
✓ |
✓ |
|
\[
{}x \left (x -2 y\right ) {y^{\prime }}^{2}-2 x y y^{\prime }-2 x y+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x \left (x -2 y\right ) {y^{\prime }}^{2}+6 x y y^{\prime }-2 x y+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2} = a^{2}
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}-a^{2}+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}-3 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}-6 x^{3} y^{\prime }+4 x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}-4 a y y^{\prime }+4 a^{2}-4 a x +y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}-\left (1+x \right ) y y^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}+2 x y y^{\prime }+x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}+2 x y y^{\prime }+a -y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}-2 x y y^{\prime }-x^{2}+2 y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}-2 x y y^{\prime }+a -x^{2}+2 y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}+2 a x y y^{\prime }+\left (a -1\right ) b +a \,x^{2}+\left (1-a \right ) y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (1-y^{2}\right ) {y^{\prime }}^{2} = 1
\] |
✓ |
✓ |
|
\[
{}\left (a^{2}-y^{2}\right ) {y^{\prime }}^{2} = y^{2}
\] |
✓ |
✓ |
|
\[
{}\left (a^{2}-2 a x y+y^{2}\right ) {y^{\prime }}^{2}+2 a y y^{\prime }+y^{2} = 0
\] |
✗ |
✗ |
|
\[
{}\left (\left (1-a \right ) x^{2}+y^{2}\right ) {y^{\prime }}^{2}+2 a x y y^{\prime }+x^{2}+\left (1-a \right ) y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (\left (-4 a^{2}+1\right ) x^{2}+y^{2}\right ) {y^{\prime }}^{2}-8 a^{2} x y y^{\prime }+x^{2}+\left (-4 a^{2}+1\right ) y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (\left (-a^{2}+1\right ) x^{2}+y^{2}\right ) {y^{\prime }}^{2}+2 a^{2} x y y^{\prime }+x^{2}+\left (-a^{2}+1\right ) y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right )^{2} {y^{\prime }}^{2} = y^{2}
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right )^{2} {y^{\prime }}^{2}-\left (x^{2}-x y-2 y^{2}\right ) y^{\prime }-y \left (x -y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}\left (a^{2}-\left (x -y\right )^{2}\right ) {y^{\prime }}^{2}+2 a^{2} y^{\prime }+a^{2}-\left (x -y\right )^{2} = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{2} {y^{\prime }}^{2}+2 x y y^{\prime }-1+x^{2}+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}3 y^{2} {y^{\prime }}^{2}-2 x y y^{\prime }-x^{2}+4 y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{2} {y^{\prime }}^{2}+2 \left (1+3 x \right ) x y y^{\prime }+3 x^{3} = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-4 y^{2}\right ) {y^{\prime }}^{2}+6 x y y^{\prime }-4 x^{2}+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}9 y^{2} {y^{\prime }}^{2}-3 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}\left (2-3 y\right )^{2} {y^{\prime }}^{2} = 4-4 y
\] |
✓ |
✓ |
|
\[
{}\left (-a^{2}+1\right ) y^{2} {y^{\prime }}^{2}-3 a^{2} x y y^{\prime }-a^{2} x^{2}+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (a -b \right ) y^{2} {y^{\prime }}^{2}-2 b x y y^{\prime }-a b -b \,x^{2}+y^{2} a = 0
\] |
✓ |
✓ |
|
\[
{}a^{2} \left (b^{2}-\left (c x -a y\right )^{2}\right ) {y^{\prime }}^{2}+2 a \,b^{2} c y^{\prime }+c^{2} \left (b^{2}-\left (c x -a y\right )^{2}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x y^{2} {y^{\prime }}^{2}-y^{3} y^{\prime }+x \,a^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x y^{2} {y^{\prime }}^{2}+\left (-y^{3}-x^{3}+a \right ) y^{\prime }+x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{2} {y^{\prime }}^{2}-y^{3} y^{\prime }-a = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{2} {y^{\prime }}^{2} x^{2} = \left (x^{2}+y^{2}\right )^{2}
\] |
✓ |
✓ |
|
\[
{}4 y^{3} {y^{\prime }}^{2}-4 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}3 x y^{4} {y^{\prime }}^{2}-y^{5} y^{\prime }+1 = 0
\] |
✓ |
✓ |
|
\[
{}9 x y^{4} {y^{\prime }}^{2}-3 y^{5} y^{\prime }-a = 0
\] |
✓ |
✓ |
|
\[
{}9 \left (-x^{2}+1\right ) y^{4} {y^{\prime }}^{2}+6 x y^{5} y^{\prime }+4 x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3} = b x +a
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3} = a \,x^{n}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}+x -y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3} = \left (a +b y+c y^{2}\right ) f \left (x \right )
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3} = \left (y-a \right )^{2} \left (y-b \right )^{2}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}+f \left (x \right ) \left (y-a \right )^{2} \left (y-b \right )^{2} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}+f \left (x \right ) \left (y-a \right )^{2} \left (y-b \right )^{2} \left (y-c \right )^{2} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}+y^{\prime }+a -b x = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}+y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}+y^{\prime } = {\mathrm e}^{y}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}-7 y^{\prime }+6 = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}-x y^{\prime }+a y = 0
\] |
✗ |
✓ |
|
\[
{}{y^{\prime }}^{3}+2 x y^{\prime }-y = 0
\] |
✗ |
✓ |
|
\[
{}{y^{\prime }}^{3}-2 x y^{\prime }-y = 0
\] |
✗ |
✓ |
|
\[
{}{y^{\prime }}^{3}-a x y^{\prime }+x^{3} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}+a x y^{\prime }-a y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}-\left (b x +a \right ) y^{\prime }+b y = 0
\] |
✓ |
✓ |
|